Using a self-organizing map to identify group-specific movement patterns during running - Hoerzer, S.; Tscharner, V.; Nigg, B. M. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purposes of this study were (a) to use a self-organizing map to identify groups of people with a similar movement pattern, (b) to associate these groups with characteristics related to age and gender, and (c) to investigate whether these groups require specific footwear features to improve comfort. The movement patterns of 88 subjects during 5 running trials were collected. A self-organizing map was used to identify groups with group-specific movement patterns. The identified groups had specific footwear requirements with respect to comfort, which was only partially explained by the age characteristics of these groups. This study demonstrated how groups of people with specific needs regarding footwear comfort can be identified by their movement pattern.